Multi-wavelength erbium-doped fiber laser assisted by four-wave mixing effect - Harun, Sulaiman Wadi; Parvizi, Roghaieh; Shahi, Sharifeh; Ahmad, Harith (IOP Publishing, 2009)
Multi-wavelength erbium-doped fiber laser (EDFL) is demonstrated using a piece of a bismuth-based erbium-doped fiber (Bi-EDF) in a simple ring resonator. The proposed EDFL is able to generate up to 17 lines with a constant channel spacing of 0.41 nm at 1615.5 nm region using only a piece of 215 cm long of Bi-EDF as both linear and nonlinear gain medium. However, the number of lines reduces to two with the use of 49 cm long of Bi-EDF. The multi-wavelength generation is due to oscillating Bi-EDF laser lines which interacts each other to create new photons at other frequency via four-wave mixing process. The multi-wavelength EDFL is stable at room temperature and also compact due to use of only a very short length of gain medium.